TEACHING PRAGMATIC COMPETENCE: THE CASE OF HEDGING - Askarova G.X. (PEDAGOGS, 2024)
Abstract. Competence-based language teaching which has become an integral part of teaching foreign languages at the present moment is paid attention to. Basic language competences are distinguished highlighting communicative competence which demonstrates a student’s ability to use a foreign language in such a way that will be appropriate from the point of view of linguistics, socio-linguistics and pragmatics. Teaching students’ pragmatic competence in general and the use of hedges in particular is focused on. The interpretation of hedges and their classification are analysed. Awareness-raising tasks such as identification, cross- linguistic comparisons, reconstruction, reformulation and metalinguistic discussion as a method of teaching learners’ pragmatic competence are considered.